1994
DOI: 10.1021/bi00209a006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Analysis of Terminal Steps in Bacteriochlorophyll a Biosynthesis: Characterization of a Rhodobacter capsulatus Strain That Synthesizes Geranylgeraniol-Esterified Bacteriochlorophyll a

Abstract: Site-directed mutational analysis of the Rhodobacter capsulatus photosynthesis gene cluster was undertaken in order to identify and characterize genetic loci involved in bacteriochlorophyll a biosynthesis. A mutant in orf304 was shown to accumulate the tetrapyrrole intermediate "bacteriochlorophyllide a" which is a tetrapyrrole that has a bacteriochlorophyll a ring structure without the presence of an esterifying alcohol. A mutant in orf391 is shown to synthesize bacteriochlorophyll a that is esterified with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
75
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 34 publications
3
75
0
Order By: Relevance
“…Detailed investigations of the properties of chlorophyll synthase became feasible after demonstration that the bchG gene of Rhodobacter capsulatus encodes bacteriochlorophyll synthase (Bollivar et al, 1994), and the G4 gene (later named ChlG gene) of Arabidopsis thaliana encodes chlorophyll synthase (Gaubier et al, 1995). The recombinant enzyme, produced by expression of the bchG from R. capsulatus in Escherichia coli, specifically accepted bacteriochlorophyllide but not Chlide, while the analogous expression of the chlG gene from Synechococcus sp.…”
mentioning
confidence: 99%
“…Detailed investigations of the properties of chlorophyll synthase became feasible after demonstration that the bchG gene of Rhodobacter capsulatus encodes bacteriochlorophyll synthase (Bollivar et al, 1994), and the G4 gene (later named ChlG gene) of Arabidopsis thaliana encodes chlorophyll synthase (Gaubier et al, 1995). The recombinant enzyme, produced by expression of the bchG from R. capsulatus in Escherichia coli, specifically accepted bacteriochlorophyllide but not Chlide, while the analogous expression of the chlG gene from Synechococcus sp.…”
mentioning
confidence: 99%
“…In Rhodobacter capsulatus, a closely related bacterium, sequencing of the entire photosynthesis gene cluster (3), followed by directed mutational analysis of selected loci (8), has identified two genes, bchG and bchP, as responsible for the phytylation of Bchlide. It was proposed that the product of the bchG gene performs an initial esterification of Bchlide with geranylgeranyl pyrophosphate (GGPP), an activated form of the C 20 alcohol, geranylgeraniol (GG), and that this alcohol moiety is then reduced sequentially to phytol by the product of bchP (Fig.…”
mentioning
confidence: 99%
“…Our results, using a genetic approach to alter pigment composition, show that BchlaP does substitute for BchlaGG in vivo, in both the LH1 and RC complexes. Bollivar et al (10) working in the other direction by substituting native BchlaP with BchlaGG in Rb. capsulatus, concluded that both the light-harvesting and photochemical functions of the LH1 and RC complexes were unaffected.…”
Section: Alteration Of Pigment Synthesis In a Transconjugant Strain Omentioning
confidence: 99%
“…BchlaGG is a biosynthetic precursor of BchlaP, and the product of a single gene is responsible for the three steps (Fig. 1A) necessary for reducing BchlaGG to BchlaP (10,12,13). This gene, bchP, encodes the enzyme BchlaGG reductase and resides among other photosynthesis-related genes in a photosynthesis gene cluster (12,14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation